PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN GOOGLE SITES DALAM PEMBELAJARAN TEKS BIOGRAFI KELAS X SMA - Hapsary Ratnadewati; riswanda Himawan; Hermanto (LPMP Provinsi DKI Jakarta, 2023)
The development of technology and information in this era certainly affects the increasingly advanced learning media, but not all learning activities use modern and up-to-date learning media. Based on this, researchers are interested in developing learning media based on Google Sites in learning biographical texts for class X at MA Muhammadiyah 1 Yogyakarta. In this study, researchers used a research and development (R&D) research model with the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The research technique used is interview and questionnaire technique. This study obtained data sources from a team of experts (material experts, media experts, and teaching experts (teachers)) and user groups (students). The results of this study stated that the development of learning media based on Google Sites in the biographical text of class X SMA / MA obtained